(untitled) (Research, Society and Development, 2020)
Population growth has accelerated the consumption of electricity, generated mainly from non-renewable sources of energy. The imminent scarcity of these sources, together with the intensification of the emission of greenhouse gases has led to concern about meeting the country’s energy needs. Investing in renewable sources of energy is essential to modifying this energy matrix and improving the country’s electrical grid. This work seeks to expand studies of Surface Geothermal Energy, which remains relatively unknown in Brazil, by monitoring the ground temperature of the city of Naviraí, MS at depths of 0.0 m (ambient temperature), 2.0 m, 4.0 m, and 6.0 m. The measurements were made using our own methodology, and the results show that the ground temperature tends to be stable as depth increases, which illustrates its great capacity to store heat, making it useful in dissipating heat in the summer and also as a source of heat in winter. Our studies show a stable temperature of 25.6ºC at a depth of 6.0 meters, thermal diffusivity of 0.468 x 10-6 m2 x s-1, and a temperature wave propagation velocity of 0.744 x 10-6 m x s-1 to the red oxisol soil in the analyzed region.